Respuesta :

Hello!

We have the expression below:

[tex]\cos (\frac{\pi}{2})\cos (\frac{3\pi}{10})-\sin (\frac{\pi}{2})\sin (\frac{3\pi}{10})[/tex]

Let's remember how we can use the sum identity formula:

[tex]\cos (a+b)=\cos (a)\cos (b)-\sin (a)\sin (b)[/tex]

Knowing it, let's use this property:

[tex]\cos (\frac{\pi}{2})\cos (\frac{3\pi}{10})-\sin (\frac{\pi}{2})\sin (\frac{3\pi}{10})=\cos (\frac{\pi}{2}+\frac{3\pi}{10})[/tex]

Let's solve the sum:

[tex]\cos (\frac{\pi}{2}+\frac{3\pi}{10})=\cos (\frac{5\pi+3\pi}{10})=\cos (\frac{8\pi}{10})[/tex]

We can simplify it by two:

[tex]\cos (\frac{8\pi}{10})=\cos (\frac{4\pi}{5})[/tex]

Answer:

cos(4pi/5)

ACCESS MORE
EDU ACCESS
Universidad de Mexico